Cybersecurity enhancement in the field of eHealth system development in Ukraine - I. Parfonova; O. Zinchenko (Medičnì Perspektivi)
Today, more than ever, cybersecurity issues are crucial in all industries and sectors, yet healthcare remains the most vulnerable. This work aims to analyze the state of cybersecurity in the most successful European countries and to outline the main steps for strengthening cybersecurity in Ukraine's electronic healthcare system. A review of literature on electronic healthcare and cybersecurity in Europe and Ukraine was conducted using Web of Science, SCOPUS, Google Scholar, and legislative databases from each of the analyzed European countries, covering a total of 49 sources from 2020 to 2024. The search was conducted using scientific terms such as “eHealth system”, “cyberattack”, “cybersecurity”, “medical information systems”, “EU4 Health”, “electronic healthcare”, “digital healthcare services”, “Ministry of Health”, “confidential information”, “legislative framework”. A total of 83 sources were initially selected and reviewed. After systematizing the gathered information, 55 of the most relevant sources were retained. Exclusion criteria included publications that did not align with the purpose of this review. The methods used included bibliographic, analytical, and forecasting. The analytical method was applied to compare Ukraine’s approach to ensuring cybersecurity in electronic healthcare with those of countries such as Estonia, Germany, France, and the United Kingdom, allowing the identification of key differences and potential improvements for Ukraine's system. Additionally, the forecasting method was used to assess future initiatives and plans in eHealth cybersecurity that should be implemented to further develop Ukraine’s protective systems. First, a clear concept of “cybersecurity of electronic healthcare” was formulated, identifying its key components. Second, the establishment of a regulatory framework was proposed to detail the aspects of cybersecurity in electronic healthcare, including guidelines and methods for supporting and improving protection systems in medical institutions. It is recommended to incorporate these provisions into the laws “On Cybersecurity” and “Fundamentals of Ukrainian Legislation on Healthcare” to enhance the effectiveness of cybersecurity measures in healthcare. Thirdly, we analyze the effectiveness of the most common cybersecurity tools and provide recommendations for their use in Ukraine: introducing regular backups for all medical systems, setting up firewalls, centralized IDS/IPS systems, mandatory data encryption, enhanced VPN authentication, automated threat monitoring systems, and engaging experts to ensure comprehensive cybersecurity of medical institutions. This will help to preserve significant amounts of confidential information and ensure the possibility of recovering lost data. The need to adapt the best European practices to the special conditions in Ukraine to work confidently in the face of potential and real threats was emphasized, which will allow timely response to new challenges and ensure cybersecurity.